105: SURGICAL DISSECTION DOES NOT INCREASE FREE CANCER CELLS (FCC) IN PERITONEAL LAVAGE OF PATIENTS FOLLOWING D2 GASTRECTOMY. (23rd April 2022) - Geca, K; Rawicz-Pruszynski, K; Sedlak, K; Mlak, R; Polkowski, W
Abstract: Background and aim: Peritoneal free cancer cells (FCC) in patients with gastric cancer (GC) is poor prognostic factor. D2 gastrectomy dissection may induce exfoliated FCC spread from primary tumour or involved lymph nodes (LN). Conventional cytology for FCC detection has several limitations, and prophylactic use of extensive intraoperative peritoneal lavage (IPL) does not improve survival. A prospective single-arm observational study was conducted to verify whether D2 gastrectomy causes an increase of FCC in peritoneal lavage as in patients with GC following D2 gastrectomy. Methods: Thirty GC patients underwent D2 gastrectomy, followed by objective quantitative measurements of CK19 mRNA level reflecting FCC with One-Step Nucleic Acid Amplification (OSNA) assay. The IPL with 3000 cc of saline was performed twice after: (1) gastrectomy with D2 lymphadenectomy; and (2) alimentary tract reconstruction. The IPL samples were analysed by initial cytology and four (1–4) consecutive OSNA assays (Figure 1). Three patients were excluded due to positive cytology in samples obtained after laparotomy. Results: Initial OSNA measurement (1) revealed positive results (≥24.6 cCP/μl) in 7 (29.6%) patients. Subsequent OSNA measurements revealed a significant decrease in the FCC level after removal of the primary tumour with regional LNs (D2 gastrectomy) (1 vs 2; medians [95%CI]: 4.6 [1.1–18.5] vs. 0.00004 [0–0.2] cCP/μl; P = 0.0012). The first IPL induced non-significant increase in the FCCs (2 vs 3, medians [95%CI]: 0.00004 [0–0.2] vs 0 [0–0.5] cCP/μl; P = 0.3300), but the second IPL reversed it to normal levels (3 vs 4, medians [95%CI]: 0 [0–0.5] vs 0 [0–0] cCP/μl; P = 0.0.0574). At this point of operation, additional finding was a trend toward temporal increase of FCC in patients with LN involvement (pN1–3)(2 vs 3; medians [95%CI]: 0 [0–0.2] vs 0 [0–42.8] cCP/μl; P = 0.0674). One patient was still positive (FCC) at the end of operation as measured by OSNA (4). Conclusion: D2 Gastrectomy does not induce increase in the peritoneal FCCs. Temporal intraoperative increase in peritoneal FCC after the IPL may be observed, especially in tumours with LN metastases. At least two consecutive IPLs (with min. 3000 mL of saline) are necessary to reverse temporal increase of peritoneal FCC.